1999
DOI: 10.1016/s0014-5793(99)00289-6
|View full text |Cite
|
Sign up to set email alerts
|

The titrations of Asp‐85 and of the cation binding residues in bacteriorhodopsin are not coupled

Abstract: An outstanding problem relating to the structure and function of bacteriorhodopsin (bR), which is the only protein in the purple membrane of the photosynthetic microorganism Halobacterium salinarium, is the relation between the titration of Asp-85 and the binding/unbinding of metal cations. An extensively accepted working hypothesis has been that the two titrations are coupled, namely, protonation of Asp-85 (located in the vicinity of the retinal chromophore) and cation unbinding occur concurrently. We have ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…36 Furthermore, it was shown that the titrations of Asp85 and of the cation binding residues in BR are uncoupled, excluding direct binding of the cation to Asp85. 37 Further supporting the notion that the binding occurs at the membrane surface are solid-state NMR analyses indicating that cation binding effects Ala196, located in the E−F interhelical loop. 38 A study using eosin dye covalently bound to the protein suggested that the cations do not bind to specific sites and bind equally to both membrane surfaces and negatively charged lipids.…”
mentioning
confidence: 72%
“…36 Furthermore, it was shown that the titrations of Asp85 and of the cation binding residues in BR are uncoupled, excluding direct binding of the cation to Asp85. 37 Further supporting the notion that the binding occurs at the membrane surface are solid-state NMR analyses indicating that cation binding effects Ala196, located in the E−F interhelical loop. 38 A study using eosin dye covalently bound to the protein suggested that the cations do not bind to specific sites and bind equally to both membrane surfaces and negatively charged lipids.…”
mentioning
confidence: 72%
“…Both of these proposals leave the Asp-85 group protonated in the blue membrane and, therefore, block the proton acceptor in the photocycle but by different means. Another study has shown that the titrations of the Asp-85 and the color-controlling site are not coupled (43). It has become a difficult task to assign whether there is a cation in the interior of the protein and, thus, to explain the exact role of the cation in the proton-pumping mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…An older ESR study found 5 Mn 2ϩ binding sites with fairly high affinities (Dunach et al, 1987). It was also postulated that the titration of Asp85 and the color-controlling site are not coupled (Fu et al, 1997;Eliash et al, 1999). The differences observed in the high-affinity sites for Ca 2ϩ and Mn 2ϩ suggest that their binding to bR are not identical, and may regulate the color differently.…”
Section: Binding Sites Of the Different Cations To Bbrmentioning
confidence: 99%